2004
DOI: 10.1159/000075986
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Reconstruction Surgery for Congestive Heart Failure

Abstract: The significant increase in the prevalence of heart failure in the United States has made this disease a major health problem. The continued shortage of donor organs has prevented heart transplantation from becoming an effective solution for the treatment of end-stage heart failure, and as a result, surgical treatments for heart failure have been reexamined. Surgical therapies represent the evolution of conventional operations, such as coronary artery bypass surgery, and the application of the more novel left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Registry data confirms collaborative information from the RESTORE multicenter cohort [2], and Dor [3] who launched this surgical evolution. Furthermore, these functional and mortality late findings are unachievable by CABG with or without mitral valve procedures [4][5][6].…”
Section: Editorial Commentsupporting
confidence: 66%
See 1 more Smart Citation
“…Registry data confirms collaborative information from the RESTORE multicenter cohort [2], and Dor [3] who launched this surgical evolution. Furthermore, these functional and mortality late findings are unachievable by CABG with or without mitral valve procedures [4][5][6].…”
Section: Editorial Commentsupporting
confidence: 66%
“…Thrombus was removed, infarcted nonviable tissue was resected, and the scar was excluded, generally by the use of a double cerclage circular closure [2]. Pericardial or Dacron patches were used as required, generally for those patients with a calcified aneurysm in whom the purse string sutures may not create a neck, or in patients with a small left ventricular cavity, to avoid creating too small a cavity [3]. A sizing balloon device was not used.…”
Section: Surgical Techniquementioning
confidence: 99%
“…However, the in-hospital mortality was 5.5% bearing in mind that the Logistical EuroSCORE was 13.8% for the cohort. The in-hospital mortality in other series varies from 2.8 to 13%, influenced by the case selection, operative techniques, and experience at different units [4,21,22]. The five-year survival is similar compared to other published data at 84.7% with slightly better 10-year outcomes at 79.1%.…”
Section: Discussionmentioning
confidence: 51%
“…The 30-day mortality was signifi cantly higher after MR surgery but there was no signifi cant difference in the survival rates between the two groups during the 5-year period, and MR was not found to be an independent predictor of late mortality. Lee et al (22) supported the opinion that MR degree was not associated with long-term survival after SVR. Menicanti et al (23) suggested that SVR, performed with or without CABG and with or without MV surgery, signifi cantly reduced LV volumes and improved LV EF; however, a signifi cant increase in LV volumes and MR degree was observed afterward.…”
Section: Discussionmentioning
confidence: 92%